Characterization of monoclonal antibody specificities against conformational epitopes of dengue NS1 glycoprotein. - Cheng, Wei. (2009)
Dengue is one of the most threatening mosquito-transmitted viral diseases in tropical areas. During infection, one of the disease markers, non-structural protein 1 (NS1), can be detected in the sera of infected subjects, and its serum concentration correlates with the disease severity. However, its role in dengue pathogenesis is still unclear. The aim of this study is to characterize the specificities of 23 previously generated anti-NS1 monoclonal antibodies (mAbs) against the conformational epitopes of NS1. In this study, I used error-prone PCR to introduce mutations to NS1 gene. Then the mAbs were closely explored for their reactivity against mutant NS1 expressed on phoenix cell surface using flow cytometry. As a result, 19 mutated NS1 which caused some mAbs lose reactivity compared to wild type (wt) NS1 were selected for DNA sequencing, and the mutations were mapped around 12 critical Cysteines and on three putative domains of NS1. We believe that these identified amino acids can either be the conformational epitopes of the mAbs, or their mutations lead to conformational change in NS1, which mask the conformational epitopes of the mAbs. After characterization of their specificities, these mAbs can be explored to facilitate the crystallization of the still unknown NS1 structure.